PENGEMBANGAN MUTLIMEDIA INTERAKTIF ANDROID MATEMATIKA UNTUK SISWA SMA - Maryam, Isnaeni (Kadikma, 2022)
The purpose of this study was to determine the development of android-based interactive multimedia learning media in mathematics class XII SMA and to determine the feasibility of the media that had been developed. This type of research is research and development (R&D). The model used is the analysis, design, development, implementation, evaluation (ADDIE) model. Data collection instruments in the form of validation sheets, questionnaires and tests. The data analysis technique used is descriptive qualitative analysis. Learning media that has been developed using the ADDIE model based on the results of the assessment of material experts with an average value of 4.42 with a very valid category and by media experts obtaining an average value of 4 with a very valid category, the practicality of the media by students obtains results the average score of 88% with the practical category based on the large group test and the effectiveness of the media obtained an average score of 81,935 with the effective category. The development of android-based interactive multimedia learning media is declared feasible to be used in the learning process. Keyword: android, multimedia learning media, mathematics